Strontium substitution in apatitic CaP cements effectively attenuates osteoclastic resorption but does not inhibit osteoclastogenesis. (June 2016) - Schumacher, M.; Wagner, A.S.; Kokesch-Himmelreich, J.; Bernhardt, A.; Rohnke, M.; Wenisch, S.; Gelinsky, M.
Graphical abstract: Abstract: Strontium ions were discovered to exert a dual effect on bone turnover, namely an inhibition of cell-driven bone resorption and a simultaneous stimulation of new bone tissue formation. A variety of strontium containing calcium phosphate bone cements (SrCPC) have been developed to benefit from both effects to locally support the healing of osteoporotic bone defects. While the stimulating effect of strontium modification on bone forming cells has been demonstrated in a number of studies, this study focuses on the inhibition and/or reduction of osteoclastogenesis and osteoclastic resorption by a strontium substituted calcium phosphate bone cement (SrCPC). Human peripheral blood mononuclear cells (PBMC) were differentiated into osteoclasts in the presence of different Sr 2+ -concentrations as well as on the surface of SrCPC disks. Osteoclastogenesis of PBMC was shown to be merely unaffected by medium Sr 2+ -concentrations comparable to those released from SrCPC in vitro (0.05–0.15 mM). However, an altering effect of 0.1 mM strontium on the cytoskeleton of osteoclast-like cells was shown. In direct contact to SrCPC disks, these cells exhibited typical morphological features and osteoclast markers on both RNA and protein level were formed. However, calcium phosphate resorption was significantly decreased on strontium-containing cements in comparison to a strontium-free control. This was accompanied by an intracellular accumulation of strontium that increased with substrate strontium content as demonstrated by Time of Flight Secondary Ion Mass Spectrometry (ToF-SIMS). This study illustrates that SrCPC do not inhibit osteoclastogenesis but significantly attenuate osteoclastic substrate resorption in vitro . Statement of Significance: Strontium ions have been shown to promote bone formation and inhibit bone resorption. Therefore strontium is successfully used in the treatment of osteoporosis and also inspired the development of strontium-containing strontium/calcium phosphate bone cements (SrCPC). Studies have shown the positive effects of SrCPC on bone formation, however, the inhibiting effect of strontium on bone resorption in the context of such cements has not been shown so far. We found that the formation of bone-resorbing osteoclasts is not inhibited, but that their resorption activity is decreased in contact to SrCPC. The former is important since those cells play an important role in the bone cell signaling. The latter is a key requirement in osteoporosis therapy, which addresses excess bone resorption.